Journal of Emergency Nursing July 2015, Volume 41, Number 4 - Emergency Nurses Association (Elsevier, 2015)
-Aneurysmal Subarachnoid Hemorrhage: A Potentially Lethal Neurological Disease -Early Revisit to the Emergency Departement: An Integrative Review -Mitigating Nursing Based in Management of Intoxicated and Suicidal Patients -Nursing Ethics and Disaster Triage: Applying Utilitarian Ethtical Theory -Assessing Patient Decision-Making Capacity: It's About the thought Process -Emergency Nursing Triage: Keeping it Safe -Southern Hospitality: How We Changed the NPO Practice in the Emergency Departement -Relationship Between Empathy and Well-Being Among Emergency Nurse -To Foley or Not to Foley: Emergency Nurses Perceptions of Clinical Decision Making in the Use of Urinary Catheters in the Emergency Depatement -An Asian Woman with Upper Arm Burns -Pediatric Mock Codes: An Evidence-Informed Focused Pediatric Resuscitation Program -Insulin Pens: Single Patient Use is Mandatory for Safety -Emergency Nursing Review Questions: July 2015 -Dischrge Texting: The Evolution of ED Callbacks - An Older Adult-Taking the Heat -Handle with Care: Preventing Abusive Head Trauma